Understanding the Process of Medical Referral: Putting the findings into perspective - Muzzin, Linda J. (1992)
In a qualitative study of 50 Canadian referrals, the family physician appeared to mediate between the patient, who often initiates the process, and the specialist, according to the specialist's availability and skills. Referrals will probably escalate unless the family physician is able to negotiate for more responsibility and respect and to convince patients of the limits of medicine.